Examining the relationship between job demands, job resources and work engagement among academics in Malaysia - Nur Hafizah, Sukhri (2015)
This study examines the direct relationship between workload, work pressure, autonomy, social support and performance feedback and work engagement. A total of 380 questionnaire were personally distributed to respondents from three universities, namely Universiti Utara Malaysia, Universiti Malaysia Perlis dan Universiti Teknologi MARA after permission was granted by the university’ management. Out of 380 questionnaire distributed, only 181 questionnaire were returned, representing a response rate of 47.63%. However, only 176 were usable for further analysis. Hypotheses for direct relationship was tested using multiple regression analyses. Results showed that only social support was positively related to work engagement. In the study, work pressure was hypothesized to be negatively related with work engagement, but the results show the opposite. Implications of the findings, potential limitations, and directions for future research are discussed.